2017
DOI: 10.1007/s10549-017-4298-1
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of adding digital breast tomosynthesis to digital mammography for breast cancer screening focused on cancer characteristics: a meta-analysis

Abstract: Adding DBT to FFDM enabled detection of early invasive breast cancer that might have been missed with FFDM alone. Knowing which cancer characteristic DBT detects may allow it to play a complementary role in predicting long-term patient outcomes and facilitate treatment planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 34 publications
9
38
0
Order By: Relevance
“…However, the numbers of detected breast cancers were too small for meaningful statistical comparisons. While initial studies suggested that the increased detection rate of tomosynthesis mostly involved invasive breast cancer, our results are similar to the preliminary findings of a more recent randomised controlled trial which found that tomosynthesis increased the detection of both invasive and in situ malignancies . More frequent cancer detection by tomosynthesis screening than in standard 2D mammography could indicate that it is more sensitive than standard mammography, but if it reflects increased detection of indolent malignancy it may not be associated with improved health outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…However, the numbers of detected breast cancers were too small for meaningful statistical comparisons. While initial studies suggested that the increased detection rate of tomosynthesis mostly involved invasive breast cancer, our results are similar to the preliminary findings of a more recent randomised controlled trial which found that tomosynthesis increased the detection of both invasive and in situ malignancies . More frequent cancer detection by tomosynthesis screening than in standard 2D mammography could indicate that it is more sensitive than standard mammography, but if it reflects increased detection of indolent malignancy it may not be associated with improved health outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Recall rate was reduced when using DBT compared to DM alone in screening studies using two study groups (RR = 0.72, 95% CI 0.64-0.80), though heterogeneity across studies was very high Almost all of the reviews in the literature comparing DBT with DM in BC screening do not distinctly report on women with dense breasts. One review, not restricted to women with dense breasts, reported that DBT with DM increased CDR with a RR of 1.29 (95% CI 1.16-1.43) (Yun et al [31]) which is comparable to our estimate. We identified only two reviews reporting on women with dense breasts, one was a quantitative rapid review and one was a narrative review without analyses [14,15].…”
Section: Discussionsupporting
confidence: 88%
“…Almost all of the reviews in the literature comparing DBT with DM in BC screening do not distinctly report on women with dense breasts. One review, not restricted to women with dense breasts, reported that DBT with DM increased CDR with a RR of 1.29 (95% CI 1.16–1.43) (Yun et al [ 31 ]) which is comparable to our estimate. We identified only two reviews reporting on women with dense breasts, one was a quantitative rapid review and one was a narrative review without analyses [ 14 , 15 ].…”
Section: Discussionsupporting
confidence: 87%